Effect of surface preparation by non-directional grinding on properties of AISI D2 plasma-nitride layer - S. Rajsiri (2018)
This research studies the properties of plasma-nitride coating on AISI D2 tool steels prepared by non-directional grinding at various finishing. In the manufacturing process, the AISI D2 was machined to size and hardened with a typical hardening process. In addition, its surface was treated with plasma nitriding. Various levels of roughness were produced as well as possible affects on the nitride coating properties. In this study, the following five conditions of grinding were performed on the hardened specimens: 1-μm diamond particle and four SiC grinding papers: P100, P240, P800, and P2500. The surface finishing with at least 0.023-μm roughness value (P800 grinding) provided a plasma-nitride layer with a moderately good hardness profile and a thick nitride layer compared with other finer finishing. This finishing process was also more economical requiring less time and manpower to create than others. Overall, this study suggests that finer surface finishing has a tendency to significantly improve the tool steels hardness profile and hardened depth. © (2013) Trans Tech Publications, Switzerland.